(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
This article briefly describes the role of new technologies in the response strategy against the CoViD-19 emergency, focusing on the different instruments implemented to slow down the spread of the disease. Taking the contact tracing app Immuni, developed by the Italian government as a case study, the paper reflects on how exceptions to general rules should be designed in order to best ensure the protection of fundamental rights.